The Correlation Between Feeding Patterns And The Incidence Of Stunting In Children Aged 0-59 Months - tutik hidayati; Rizki Citra Dewi Pratiwi (Universitas Nahdlatul Ulama Surabaya, 2022)
Stunting is one of the severe problems in Indonesia. One of its causes is a lack of nutritional intake during infancy. In addition, maternal parenting, especially in feeding patterns, will affect the children's growth and development. This study aims to determine the correlation between feeding patterns and the incidence of stunting. The research design used correlational analytics. The population was stunted children aged 0-59 months at Kalibuntu Village, Probolinggo Regency. In addition, there were 66 respondents in this study with total sampling. The independent variable was feeding patterns, while the dependent variable was the incidence of stunting. Data collection was carried out using a questionnaire on feeding patterns that respondents' mothers filled out. In addition, the authors measured respondents' height and assessed with a WHO (World Health Organization) growth chart to collect data on the incidence of stunting. Data analysis used the Spearman rank rho test. Almost half of the respondents had inappropriate feeding patterns (42.4%). In addition, most of the stunted children's height was categorized as short (85.3%). 15.2% of stunted children with inappropriate feeding patterns had very short height. In addition, 56.1% of respondents with appropriate feeding patterns were categorized as short. The Spearman rank rho test obtained p=0.000, indicating H0 was rejected and H1 was accepted. In addition, the value of the correlation coefficient was 0.439, showing a moderate correlation between both variables. In conclusion, feeding patterns correlate with the incidence of stunting among children aged 0-59 months in Kalibuntu Village, Probolinggo Regency.